Effect of Photobiomodulation Therapy Associated With Biphasic Phosphate Calcium on Bone Repair: A Histomorphometric Study in Rats - De Marco, Andréa Carvalho [UNESP] (2022)
Introduction: This study aimed to investigate the effects of photobiomodulation (PBM) therapy associated with biphasic calcium phosphate on calvaria critical defects in rats. Methods: Forty-eight (90 days old) adult male rats (Rattus norvegicus, Albinus variation, Wistar) received critical defects of 5 mm in diameter, which were made on their skull, and they were randomly assigned into the following groups: C-blood clot, B-biphasic calcium phosphate, L-photobiomodulation therapy, and B + L-biphasic calcium phosphate + photobiomodulation therapy. A low-level a gallium aluminum arsenide (GaAlAs) laser was applied in a single dose during surgery, in a wavelength of 660 nm and total energy density of 45 J/cm2. On 30th and 60th days, the animals from each group were euthanized. Histological and histomorphometric analyses were performed. Results: In 30 days, almost all specimens (C, L, B and B + L) showed bone neoformation areas in regions near the borders of the surgical defect. In 60 days, in many specimens (C, L, B, B + L), it was possible to see a narrow neoformed bone structure along almost the whole extension of the surgical defect, though it was thinner than the original calvary bone. Data were recorded as mean ± standard deviation, and after normality was tested, a suitable statistical test was applied (α = 5%). On day 60, there was a statistically significant difference when comparing the proportion of neoformation area between group L (0.52% ± 0.13) and group B + L (0.20% ± 0.08). Group L showed a difference compared with all the groups when we compared the remaining distance between the edges of neoformed bone (C × L, P = 0.0431; B × L, P = 0.0386; L × B + L, P = 0.0352), demonstrating a great defect closure. Conclusion: Our findings suggest that although biphasic calcium phosphate exerts some osteogenic activity during bone repair, PBM therapy is not able to modulate this process